Antimicrobial activity of plant extracts against carbapenem-producing Klebsiella pneumoniae and in vivo toxicological assessment. Issue 23 (16th December 2020) - Vasconcelos, Nathalie Gaebler; Vaz, Márcia Soares Mattos; Radai, Joyce Alencar Santos; Kassuya, Candida Aparecida Leite; Formagio, Anelise Samara Nazari; Graciani, Fernanda Silva; Leal, Maria Lorenza; Oliveira, Rodrigo Juliano; da Silva, Kesia Esther; Croda, Julio; Simionatto, Simone
ABSTRACT: The global spread of multidrug-resistant strains has prompted the scientific community to explore novel sources of chemicals with antimicrobial activity. The aim of the study was to examine the antimicrobial activity in vitro of 28 extracts against carbapenem-producing Klebsiella pneumoniae, individually and in combination with antibiotics and in vivo toxicological assessment of the most active product. The multi-resistant K. pneumoniae strain was submitted for phenotypic and molecular characterization. The antibacterial activity of 28 plant extracts was evaluated alone and in combination with antibiotics against this strain through the agar disk diffusion. Of these, 16 extracts showed synergism against carbapenem-producing K. pneumoniae, being that B. crassifolia extract exhibited synergism with three antibiotics. Based on this assessment, B. crassifolia- extract-induced toxicity on Swiss male mice was evaluated by administering this extract and subsequently determining apoptosis and splenic phagocytosis using the comet and micronucleus assays. The results of this study showed that B. crassifolia extract had synergistic activity promising and groups treated with B. crassifolia exhibited no genotoxic or mutagenic activity, indicating that B. crassifolia extract exerted beneficial effects and appeared safe to use at the studied concentrations.